Exertional Oxygen Requirements During Exercise Training in Advanced Interstitial Lung Disease. Issue 6 (November 2018) - Wickerson, Lisa; Brooks, Dina; Reid, W. Darlene; Singer, Lianne G.; Granton, John; Mathur, Sunita
Abstract : Purpose: Little is known about the oxygen requirements during physical exertion or exercise in individuals with interstitial lung disease (ILD). This study examined exertional oxygen requirements, the relationships between exertional oxygen use, exercise capacity and aerobic training parameters, and predictors of change in exertional oxygen requirements during pulmonary rehabilitation (PR). Methods: A retrospective study of lung transplant candidates with advanced ILD who underwent at least 4 wk of outpatient PR between 2004 and 2014 was undertaken. Data were extracted at baseline, 4 wk, and 6 mo. Exertional oxygen was prescribed during PR to support continuous, moderate-intensity aerobic training. Results: The study cohort (n = 375) had a median age of 61 y (55-66 y), were 57% male, and most were diagnosed with idiopathic pulmonary fibrosis (n = 214). A variety of oxygen delivery systems were used and exertional oxygen requirements increased after 4 wk (0.5 [0.4-0.6] vs 0.5 [0.4-0.73], P < .001, n = 375) and 6 mo (0.44 [0.36-0.5] vs 0.5 [0.4-0.55], P < .001, n = 196) of PR. A higher exertional oxygen requirement was associated with lower 6-min walk distance and lower aerobic training intensity at all time points. There were no identified predictors of the change in exertional oxygen requirements. Conclusions: Individuals with advanced ILD had high exertional oxygen requirements to participate in moderate-intensity aerobic training, which increased over time. Exertional oxygen needs may affect exercise prescription and response during PR in ILD patients. Abstract : Supplemental Digital Content is Available in the Text.This retrospective study examined exertional oxygen requirements during pulmonary rehabilitation in advanced interstitial lung disease. High oxygen supplementation was used to participate in moderateintensity aerobic training, which increased over time. Higher exertional oxygen requirements were associated with lower 6-min walk distances and lower aerobic training intensities at all time points.